Delivery of S1P receptor‐targeted drugs via biodegradable polymer scaffolds enhances bone regeneration in a critical size cranial defect. Issue 4 (17th October 2013) - Das, Anusuya; Tanner, Shaun; Barker, Daniel A.; Green, David; Botchwey, Edward A.
Abstract Biodegradable polymer scaffolds can be used to deliver soluble factors to enhance osseous remodeling in bone defects. To this end, we designed a poly(lactic‐co‐glycolic acid) (PLAGA) microsphere scaffold to sustain the release of FTY720, a selective agonist for sphingosine 1‐phosphate (S1P) receptors. The microsphere scaffolds were created from fast degrading 50:50 PLAGA and/or from slow‐degrading 85:15 PLAGA. Temporal and spatial regulation of bone remodeling depended on the use of appropriate scaffolds for drug delivery. The release profiles from the scaffolds were used to design an optimal delivery system to treat critical size cranial defects in a rodent model. The ability of local FTY720 delivery to maximize bone regeneration was evaluated with micro‐computed tomography (microCT) and histology. Following 4 weeks of defect healing, FTY720 delivery from 85:15 PLAGA scaffolds resulted in a significant increase in bone volumes in the defect region compared to the controls. A 85:15 microsphere scaffolds maintain their structural integrity over a longer period of time, and cause an initial burst release of FTY720 due to surface localization of the drug. This encourages cellular in‐growth and an increase in new bone formation. © 2013 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 102A: 1210‐1218, 2014.